(untitled) (Journal of Management and Business Education, 2025)
Purpose: This study aims to understand the impact of various leadership styles, including team leadership, situational leadership, and super leadership, on agile outcomes in the Indian IT industry. This study fills the vacuum in the literature about the interplay between leadership and emerging economies, presenting a model of leadership that is responsive to changes across different levels of agile maturity. Design/Methodology/Approach: This study employed a quantitative, analytical-descriptive design, collecting data via a structured electronic survey from 248 agile practitioners, including team members and leaders from Indian IT firms. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) Version 28, employing correlation and multiple regression analyses to examine the impacts of leadership behaviors on agile transformation outcomes. Findings: It was found that all three leadership styles have an impact on agile transformation, with super leadership having the most positive impact. The study proposes a Stage-Based Agile Leadership Model, illustrating that leadership effectiveness progresses across agile maturity stages, from situational leadership in pre-agile stages to team leadership in mid-level stages and super leadership at the highest level of agile maturity. Practical Implications: The findings suggest that one-size-fits all leadership training may be inadequate for agile transformations. Organizations should implement stage-specific leadership development programs to align leadership behaviours with the evolving needs of agile teams, enhancing adaptability and resilience. Originality/Value: This research extends the literature by introducing a dynamic, context-sensitive leadership model specifically applicable to emerging economies. It challenges the static view of leadership in agile contexts and emphasizes the importance of evolving leadership strategies for sustaining organizational agility.